(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
In the Expediente we present the Urdimento Editorial, that is, the body of editors, associate editors, thematic dossier editors, editorial board and the body the reviewers working in the issue of Urdimento. We also introduce the editorial support team.